Peran Mediasi Kepuasan Kerja Pada Pengaruh Kecerdasan Emosional Dan Lingkungan Kerja Terhadap Kinerja Pegawai - Alfonsius Nceong; Eli Hasmin; Herman Sjahruddin; Ardiansyah Halim (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to support policymakers in recognizing the elements that influence the performance of state civil servants and evaluating their job satisfaction levels. By shedding light on aspects that impact their morale and productivity, it seeks to pinpoint areas for improvement, including emotional intelligence and workplace conditions or management strategies. The purpose of this research is to investigate how job satisfaction mediates the impact of emotional intelligence and the work environment on employee performance at the Regional Development Planning Agency of Pegunungan Bintang Regency in Papua Pegunungan Province. Out of 35 employees, one did not finish the questionnaire, resulting in 34 data points that were analyzed using variance-based Structural Equation Modeling (SEM) through Partial Least Squares (PLS). This study's findings demonstrate that while emotional intelligence and the work environment significantly enhance employee satisfaction, they do not contribute to improved employee performance. In contrast, perceived job satisfaction has been shown to positively influence employee performance. The role of job satisfaction as a mediator is confirmed to lead to higher levels of employee performance.